I Have Had Enough: When and How Customer Mistreatment Leads to Coworker Undermining - Huilian, Zhou; Waqas, Muhammad; Yahya, Farzan; Ahmad Qadri, Usman; Zahid, Fatima (Frontiers in Psychology, 2022)
Service workers are more prone to experience customer mistreatment because of their frequent interactions with them. Hence, it compels them to the level where their performance is compromised. Employees who face customer mistreatment feel ill-treated and develop the desire for revenge. Based on the social exchange and displaced revenge perspective, this study examined the relationship between customer mistreatment and coworker undermining, and individual-level resource-based moderator service rule commitment (SRC) for this relationship. An analysis of time-lagged, dyadic data (81 supervisors and 410 subordinates) from the Chinese service industry confirmed that customer mistreatment significantly predicted coworker undermining. In addition, in support of the resource perspective, employees’ SRC effectively restricts an effect of customer mistreatment on coworker undermining. Finally, this study contributes to the customer mistreatment and coworker undermining literature by highlighting their relationship. This study also shows the importance of SRC in restraining the adverse effects of customer mistreatment.